2010
DOI: 10.1016/j.ipm.2010.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Ten good reasons to use the Eigenfactor™ metrics

Abstract: The Eigenfactor score is a journal influence metric developed at the Department of Biology of the University of Washington and recently introduced in the Science and Social Science Journal Citation Reports maintained by Thomson Reuters. It provides a compelling measure of journal status with solid mathematical background, sound axiomatic foundation, intriguing stochastic interpretation, and many interesting relationships to other ranking measures. In this short contribution, we give ten reasons to motivate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…[7] We preferred to use the EF Score tables from Journal Citation Reports due to the availability of other scientometric indicators in these tables. Also, JCR is still considered as a de facto standard in evaluating the scientific production, [17,18] even if recent literature revealed many limitations of this database, among which high cost, limited availability, a significant underestimation of the individual's actual citation impact (especially due to the removal of citations from PhD theses, books, and non ISI-ranked journals), poor aggregation of minor variations of the same title, limited coverage of non-English sources, incorrect appreciation of apostrophes and diacritics. [19] In order to obtain E mp we divided the value obtained to the number of articles published in the respective journal for the number of years considered for the EF.…”
Section: Discussionmentioning
confidence: 99%
“…[7] We preferred to use the EF Score tables from Journal Citation Reports due to the availability of other scientometric indicators in these tables. Also, JCR is still considered as a de facto standard in evaluating the scientific production, [17,18] even if recent literature revealed many limitations of this database, among which high cost, limited availability, a significant underestimation of the individual's actual citation impact (especially due to the removal of citations from PhD theses, books, and non ISI-ranked journals), poor aggregation of minor variations of the same title, limited coverage of non-English sources, incorrect appreciation of apostrophes and diacritics. [19] In order to obtain E mp we divided the value obtained to the number of articles published in the respective journal for the number of years considered for the EF.…”
Section: Discussionmentioning
confidence: 99%
“…We also filter out the publications at the "long tail" through number of citations and number of publications, and calculate the correlation between CPP and PPP for larger units, and find that larger research units have higher correlation between CPP and PPP. Several studies have found high correlation between citation counts and scores of PageRank-like indicators for journals (Bollen et al, 2006;Davis, 2008;Lopez-Illescas et al, 2008;Fersht, 2009;Bollen et al, 2009;Franceschet;) and for articles (Chen et al, 2007;Ma et al, 2008;Yan & Ding, 2010 submitted). In one collection, the majority of journals, authors, or articles may have similar status for popularity and prestige, while only a small portion of them have a different status, and hence it is not surprising to discover that discrepancies may occur at the local scale but cannot be reflected at the global level.…”
Section: Popularity (Number Of Citations) Vs Prestige (P-rank Score)mentioning
confidence: 99%
“…The principle idea is that the importance of a journal rises as it is cited in other journals, particularly prestigious ones (Franceschet 2010b). Thus, a journal that is frequently cited, especially in high-influence journals, is weighted more heavily and is attributed greater influence than a journal sparsely cited or cited in low-influence journals (West, Bergstrom, and Bergstrom 2010b).…”
Section: Bibliometricsmentioning
confidence: 99%
“…Thus, a journal that is frequently cited, especially in high-influence journals, is weighted more heavily and is attributed greater influence than a journal sparsely cited or cited in low-influence journals (West, Bergstrom, and Bergstrom 2010b). Three intriguing features of the Eigenfactor score are (1) its sensitivity to journal size, meaning that it is possible for larger journals to have larger scores simply because they publish more articles than smaller ones; (2) its additive quality, in that scores of multiple journals can be summed to provide a snapshot of their collective importance; and (3) its intentional exclusion of self-citations in weight assignment (Eigenfactor.org 2011;Franceschet 2010b;West, Bergstrom, and Bergstrom 2010b).…”
Section: Bibliometricsmentioning
confidence: 99%